The effect of specific exercises on determining the effectiveness of creatine, phosphorus, and volleyball serve skills. (Researcher) - Salman, Prof. Dr. Amal Subhi (Sulaimani Journal for Humanities, 2026)
The importance of this research lies in preserving energy production and preventing its waste. This can only be achieved through appropriate and suitable training to maintain energy production in players, by implementing and testing this training. Research Objectives: 1- To develop specific exercises to determine the effectiveness of creatine and phosphorus in volleyball serving skills. 2- To determine the effect of specific exercises on the effectiveness of creatine and phosphorus in volleyball serving skills. Key Findings: 1- The specific exercises had a positive effect on energy production after the breakdown of creatine and phosphorus during appropriate training. 2- The specific exercises designed by the researcher had a significant effect on developing volleyball serving skills. 3- To conduct appropriate training and study the facts related to speed and its importance in volleyball in the energy production process through the control of creatine and phosphorus. 2-5 Recommendations: 1- Adopting specific exercises is of paramount importance in energy production after the breakdown of creatine and phosphorus during appropriate training and in developing volleyball serving skills. 2- Emphasizing the necessity of appropriate training and studying the facts related to speed and its importance in volleyball in the energy production process through creatine and phosphorus control. 3- Conducting periodic laboratory tests at various levels, as this benefits their health and contributes to the continuous improvement of their performance. The importance of this research lies in maintaining energy production and avoiding excessive expenditure, which can only be achieved through proper and appropriate training to preserve the players' energy production by implementing and testing this training.
Keywords: Special exercises; creatine and phosphorus; volleyball serve skill